Changes in dendritic complexity and spine morphology in transgenic mice expressing human wild-type tau - Dickstein, Dara L. (2010)
Neurofibrillary tangles (NFTs) are composed of insoluble, hyperphosphorylated aggregates of the microtubule-associated protein tau and are present in various neurodegenerative diseases, including Alzheimer’s disease (AD). To investigate how tau affects neuronal function during NFT formation and subsequent neurodegeneration, we examined the morphology, spine density, spine type, and spine volume of layer III pyramidal neurons from the prefrontal cortex of mice expressing wild-type human tau (htau) over time. There were no significant alterations in apical dendritic arbor length in 3-, 6-, and 12-month-old htau mice; however, 12-month-old mice exhibited more complex arborization patterns. In addition, we observed a shift in spine morphology with fewer mushroom and more thin spines in both apical and basal dendrites as a function of htau accumulation. Interestingly, there was an overall decrease in volume of spines from 3 to 12 months. However, the volume of mushroom spines decreased from 3 to 6 months and increased from 6 to 12 months. This increase in complexity and branching in 12-month-old mice and the increase of volume of mushroom spines may represent compensatory mechanisms in the remaining intact neurons. As such, the accumulation of phosphorylated tau over time may contribute to the cognitive decline observed in AD by affecting neuronal structure and synaptic properties. Such alterations in dendrites and spines may result in the deterioration of neuronal function observed in AD, and provide a morphologic substrate for the relationship between synaptic integrity and cognitive decline.